2023
DOI: 10.1186/s13071-023-05900-3
|View full text |Cite
|
Sign up to set email alerts
|

Host–pathogen associations revealed by genotyping of European strains of Anaplasma phagocytophilum to describe natural endemic cycles

Julia Fröhlich,
Susanne Fischer,
Benjamin Bauer
et al.

Abstract: Background The zoonotic intracellular alpha-proteobacterium Anaplasma phagocytophilum is a tick-transmitted pathogen. The associations between vertebrate reservoirs and vectors are described as wide-ranging, and it was previously shown that the pathogenicity of A. phagocytophilum differs depending on the combination of pathogen variant and infected host species. This leads to the question of whether there are variations in particular gene loci associated with different virulence. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…An analysis of the groEL sequences in BLAST showed that all these haplotypes can be classified as European ecotypes. The obtained haplotypes did not demonstrate any high similarity (90-95%), with any of the groEL sequences present in the GenBank database from Asia, MT010579.1, MN989864 [58], MH722253, MH722254 [59], KY379956; North America, AF383227 [60], AY219849 [61], JF494840 [62], DQ680012; and Middle America, MW699686, MW699687 [63]. Interestingly, in red deer, only one haplotype of groEL was recorded, which was found to belong to ecotype I.…”
Section: Discussionmentioning
confidence: 76%
“…An analysis of the groEL sequences in BLAST showed that all these haplotypes can be classified as European ecotypes. The obtained haplotypes did not demonstrate any high similarity (90-95%), with any of the groEL sequences present in the GenBank database from Asia, MT010579.1, MN989864 [58], MH722253, MH722254 [59], KY379956; North America, AF383227 [60], AY219849 [61], JF494840 [62], DQ680012; and Middle America, MW699686, MW699687 [63]. Interestingly, in red deer, only one haplotype of groEL was recorded, which was found to belong to ecotype I.…”
Section: Discussionmentioning
confidence: 76%